Preliminary effects and feasibility of online interactive Baduanjin exercise in adults with overweight and obesity: a pilot randomized controlled trial - Yu, Yan; Wu, Jinpeng; Wu, Tongtong; Chen, Genghang; Chen, Xueyin; Liu, Shaonan; Chen, Yu; Yang, Lihong; Guo, Xinfeng (Frontiers in Endocrinology, 2025)
BackgroundOverweight and obesity are chronic conditions with severe health implications, demanding effective and sustainable management strategies. The escalated Baduanjin, an adapted form of traditional Baduanjin, is proposed as a targeted intervention for individuals with overweight and obesity, offering a potentially effective and accessible approach to weight management and overall health improvement.ObjectivesThis pilot study aimed to assess the preliminary effects and feasibility of the online interactive escalated Baduanjin exercise program, with a focus on participant engagement and acceptance.MethodsA 12-week pilot randomized controlled trial was conducted in Guangzhou, China, from June 30 to November 15, 2023, involving 50 participants with overweight and obesity. Participants were randomly allocated to the intervention group (n=26) or the control group (n=24). The intervention group received three 60-minute online interactive escalated Baduanjin exercises per week for 12 weeks, in addition to health education. The control group received only health education, delivered in three sessions over the 12-week period. The primary outcome was the change in body mass index (BMI) from baseline to week 12. Secondary outcomes included changes in waist circumference, body weight, blood glucose, lipid levels, blood pressure, quality of life, and dampness scale scores. Feasibility was assessed by participant adherence to the required intervention, and adverse events were recorded throughout the study period.ResultsCompared to the control group, the intervention group exhibited a reduction in BMI (mean ± SD: -0.54 ± 1.67 vs. -0.13 ± 0.81), body weight, diastolic blood pressure, fasting blood glucose, and triglyceride levels over the 12 weeks, though this difference was not statistically significant. However, the intervention group demonstrated significant improvements in several health parameters, including waist circumference, fatigue scale-14 (FS-14), general anxiety disorder (GAD-7), patient health questionnaire-9 items (PHQ-9), Pittsburgh sleep quality index (PSQI), and dampness scale scores. Adherence to the intervention was high, with 82% (41/50) of participants completing the trial, and no serious adverse events were reported.ConclusionThe preliminary effects and feasibility of the online interactive escalated Baduanjin for adults with overweight and obesity have been demonstrated, highlighting its potential multifaceted health benefits and high adherence.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier ChiCTR2300072981.